2020
DOI: 10.1097/rhu.0000000000001684
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Physical Activity in Patients With Fibromyalgia

Abstract: Background/Objective: The aim of this study was to identify psychological factors that influence moderate-vigorous physical activity (MVPA) participation in patients with fibromyalgia. Methods:In this secondary data analysis, 170 patients received personalized exercise plans and completed baseline and follow-up assessments of self-reported physical activity at weeks 12, 24, and 36. Structural equation modeling was used to examine the predictive strengths of psychological factors (exercise self-efficacy, percei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 44 publications
(74 reference statements)
3
15
0
Order By: Relevance
“…Therefore, these findings underlined the relevance in undertaking a therapeutic strategy focused on increasing personal control, such as PA self-efficacy. Our results support previous ones in fibromyalgia about the role of self-efficacy in exercise using self-reported measures [ 39 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, these findings underlined the relevance in undertaking a therapeutic strategy focused on increasing personal control, such as PA self-efficacy. Our results support previous ones in fibromyalgia about the role of self-efficacy in exercise using self-reported measures [ 39 ].…”
Section: Discussionsupporting
confidence: 91%
“…There is evidence about the role of self-efficacy on physical activity and exercise in both clinical and non-clinical contexts [ 34 , 35 , 36 ]. Moreover, self-efficacy is the main factor in affecting psychological and physical functioning in chronic pain patients [ 37 , 38 ] and predicting exercise and physical activity in fibromyalgia [ 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Focusing on nursing, a recent study in women with FM has shown that, for these women, exercise self-efficacy, perceived barriers, and intention to exercise are important constructs for increasing physical activity ( Kaleth et al, 2022 ). The need to reduce barriers and promote more facilitators to help patients' pain management have promoted the inclusion of non-pharmacologic treatments in nursing care plans ( Liu, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…By enhancing awareness of positive experiences such as walking, PA may increase access to new contextual information with which to reappraise current circumstances and reframe them as benign, meaningful, or even beneficial ( Flink et al, 2015 ). Navigating adversity through this "positive attitude" may ameliorate chronic negative emotionality, enhance self-efficacy of walking, and promote wellbeing by establishing a sense of coherence and meaning in life ( Hassett & Finan, 2016 ), all of which are important components of any treatment that may be included in nursing domains to improve treatment adherence in chronic pain ( Kaleth et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…We will measure psychological variables related to pain sensitivity and other main signs and symptoms, such as kinesiophobia 29 and self-efficacy. 20,30,31 For this purpose, we will use the Chronic Pain Self-Efficacy Questionnaire, in its Spanish-validated version 32 and the Tampa Scale of Kinesiophobia, also translated and validated in Spanish. 33 Finally, with Beck Depression Inventory (BDI): scale that allows us to measure depressive symptoms and severity of depression in patients older than 13 years.…”
Section: Psychological Variables and Self-efficacymentioning
confidence: 99%